Fundamentals of comparative terminology in Russian - Umarbekova Gulnora Anvarbekovna (Genius Journals, 2022)
This article provides information about the basics of comparative terminology in Russian, a glossary of terms, the level of terminology of scientific works, the frequency of use of terms.
Keywords: Russian language; terminological dictionary; terminology; comparison